Cancer stem-like cells from head and neck cancers are chemosensitized by the Wnt antagonist, sFRP4, by inducing apoptosis, decreasing stemness, drug resistance and epithelial to mesenchymal transition - Warrier, Sudha; Bhuvanalakshmi, G.; Arfuso, Frank; Rajan, G.; Milward, M.; Dharmarajan, Arunasalam (Nature Publishing Group, 2014)
Cancer stem cells (CSCs) of head and neck squamous cell carcinoma (HNSCC) are defined by high self-renewal and drug refractory potential. Involvement of Wnt/ß-catenin signaling has been implicated in rapidly cycling cells such as CSCs, and inhibition of the Wnt/ß-catenin pathway is a novel approach to target CSCs from HNSCC. In this study, we found that an antagonist of FrzB/Wnt, the secreted frizzled-related protein 4 (sFRP4), inhibited the growth of CSCs from two HNSCC cell lines, Hep2 and KB. We enriched the CD44+ CSC population, and grew them in spheroid cultures. sFRP4 decreased the proliferation and increased the sensitivity of spheroids to a commonly used drug in HNSCC, namely cisplatin. Self-renewal in sphere formation assays decreased upon sFRP4 treatment, and the effect was reverted by the addition of Wnt3a. sFRP4 treatment of spheroids also decreased ß-catenin, confirming its action through the Wnt/ß-catenin signaling pathway. Quantitative PCR demonstrated a clear decrease of the stemness markers CD44 and ALDH, and an increase in CD24 and drug-resistance markers ABCG2 and ABCC4. Furthermore, we found that after sFRP4 treatment, there was a reversal in the expression of epithelial to mesenchymal (EMT) markers with the restoration of the epithelial marker E-cadherin, and depletion of EMT-specific markers twist, snail and N-cadherin. This is the first report demonstrating that the naturally occurring Wnt inhibitor, sFRP4, can be a potential drug to destroy CSC-enriched spheroids from HNSCCs. The repression of EMT and the decrease in stemness profile further strengthen the use of sFRP4 as a potent therapeutic against CSCs